2014
DOI: 10.3390/ijerph110909273
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Related Illness among Oregon Farmworkers

Abstract: Farmworkers are particularly vulnerable to climate-sensitive health outcomes such as heat-related illness (HRI) given their tasks involve heavy exertion in an outdoor setting. The objectives of the study were to: (1) describe symptoms of HRI experienced by farmworkers and (2) explore factors associated with heat knowledge, level of concern regarding HRI, and comfort level taking breaks at work. Bilingual research staff conducted personal interviews of 100 farmworkers during July and August 2013. Data collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 11 publications
3
42
0
6
Order By: Relevance
“…always very flexible and a series of hot, warm days with reduced rainfalls increase the requirements for artificial irrigation, forcing AWs to perform their activities even during HWs [30,33,34,[45][46][47]. Not coincidentally, in our survey the daily average rate of OIs was similar from June to August, being higher in the calendar months of September and June, with the significant lack of effect for the central months of July and August, otherwise characterized by higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…always very flexible and a series of hot, warm days with reduced rainfalls increase the requirements for artificial irrigation, forcing AWs to perform their activities even during HWs [30,33,34,[45][46][47]. Not coincidentally, in our survey the daily average rate of OIs was similar from June to August, being higher in the calendar months of September and June, with the significant lack of effect for the central months of July and August, otherwise characterized by higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Available estimates suggest that the increased magnitude and frequency of extreme events would ultimately lead to a significant excess in morbidity and mortality for cardiovascular and respiratory illnesses, and that the climate changes will presumptively increase both the incidence and the severity of these effects [4][5][6][7][8][9][10][11][12], in particular in Mediterranean-like climates [13]. migrant background [33,34], part-time or seasonal workers, and "hobby farmers" (i.e., subjects running a farm as a hobby rather than as means of making a living), the number of which usually surges during hot moths and the harvest season, including subjects who otherwise spend little time outdoor [25,29,35]. Hence, many AWs may continue to work beyond a safe heat exposure limit as they are unaware of the risks associated with the heat exposure or have inappropriate knowledge of the preventive measures, as avoiding the hottest hours of the day for most strenuous physical exertion or increasing the water intake, in particular during the HWs [13,30].…”
Section: Introductionmentioning
confidence: 99%
“…Há estudos que analisam os agravos ou alterações nas respostas fisiológicas de órgãos ou sistemas do corpo humano, relacionados à exposição ao calor 17,19,23,24,25,26 . Outros trabalhos associam o calor com aumento da taxa de morbidade e mortalidade 27,28 .…”
Section: Risco De Exposição à Sobrecarga Térmica Para Trabalhadores Dunclassified
“…A sobrecarga térmica ocorre quando há desequilíbrio térmico do corpo, isto é, recebe mais calor do que pode dissipar, causando seu aquecimento acima de 38 º C. Quanto maior a temperatura do corpo, maiores são os efeitos fisiológicos provocados pelo calor. A permanência em condições térmicas desfavoráveis pode causar o estresse térmico, resultando em debilidade do estado geral de saúde, alterações das reações psicossensoriais e queda de produção 22 .Há estudos que analisam os agravos ou alterações nas respostas fisiológicas de órgãos ou sistemas do corpo humano, relacionados à exposição ao calor 17,19,23,24,25,26 . Outros trabalhos associam o calor com aumento da taxa de morbidade e mortalidade 27,28 .…”
unclassified
“…Mirabelli et al 13 reported that 94% and 40% of participants reported working in extreme heat and experiencing heat-related symptoms, respectively. Bethel and Harger14 showed that approximately 30% of participants reported having at least two heat-related symptoms. Fleischer et al 15 interviewed 405 migrant farmworkers in Georgia and reported one-third of participants experiencing three and more heat-related symptoms.…”
Section: Introductionmentioning
confidence: 99%